Maximum power available: An important concept for prediction of task failure and improved estimation of training loads in cycling - Kontro, H.; Mastracci, A.; Cheung, S.; MacInnis, M. J. (Journal of Science and Cycling, 2024)
Predicting cycling performance requires accurate quantification of the parameters of the power-duration relationship and detailed understanding of the training load-performance relationship. Existing models simplify training stress into single metrics, overlooking diverse responses to intensities and their time-dependency. The theoretical framework for the concept of Maximum Power Available (MPA) is described in this presentation. MPA is used to quantify instantaneous training stress and predict task failure in cycling. It employs a modified 3-parameter critical power model capable of fitting intermittent data while relying solely on the W` balance differential model. Rather than W` balance = 0, task failure is defined as MPA reaching the task work rate. Additionally, MPA may be used to derive more valid training load metrics when compared with other training load metrics. By acknowledging the multidimensional nature of exercise stress, this model provides a more comprehensive model for the power-duration and the training load-performance relationship, with the potential to facilitate more effective training program design and performance optimization.